Responsibilities of Islamic Education Institutions - Rindi Irma Audia; Putri Agil (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
Islamic educational institutions play an important role in shaping individuals morally and intellectually, aiming to benefit themselves, society and the environment as needed. This research explores the roles and responsibilities of three types of Islamic education institutions in Indonesia: formal, non-formal and informal. It emphasizes that Islamic education goes beyond academics to include moral and spiritual dimensions, which distinguish it from other education systems. The research aims to understand how each type of institution fulfills its responsibilities towards students and society, identifying challenges and opportunities in integrating Islamic values into modern education. This research uses a qualitative descriptive method, focusing on a literature review. Data from books, journals and relevant sources describe the roles and responsibilities of the institutions, showing that formal institutions such as Islamic schools and universities provide structured education that includes academics, character and religious understanding. Non-formal institutions offer flexible education for those who cannot attend formal education full-time, while informal institutions reinforce religious and social values in a family or community setting.